Effect of the Repetitions-In-Reserve Resistance Training Strategy on Bench Press Performance, Perceived Effort, and Recovery in Trained Men. Issue 1 (January 2022) - Mangine, Gerald T.; Serafini, Paul R.; Stratton, Matthew T.; Olmos, Alex A.; VanDusseldorp, Trisha A.; Feito, Yuri
Abstract : Abstract: Mangine, GT, Serafini, PR, Stratton, MT, Olmos, AA, VanDusseldorp, TA, and Feito, Y. Effect of the repetitions-in-reserve resistance training strategy on bench press performance, perceived effort, and recovery in trained men. J Strength Cond Res 36(1): 1–9, 2022—This study examined the effects of the repetitions-in-reserve (RIR) strategy on resistance exercise performance, perceived effort, and recovery. Fourteen resistance-trained men (24.6 ± 3.0 years, 176 ± 5 cm, 85.7 ± 14.0 kg) completed 2 bench press protocols in a randomized crossover fashion. The protocols consisted of 4 sets at 80% of 1 repetition maximum (1RM) to a self-reported 3-RIR and a fifth set to failure or all 5 sets to failure (0-RIR). Barbell kinetics (velocity, rate of force development, and impulse), repetition volume, total work, and ratings of perceived exertion (RPE) were quantified on each set. Barbell kinetics were reassessed during one set of 3 repetitions at 80% 1RM completed at 24-hour, 48-hour, and 72-hour postexercise. Blood samples were collected before and after exercise at 6 hours, 24 hours, 48 hours, and 72 hours and analyzed for concentrations of creatine kinase (CK). Separate, 2-way repeated-measures analysis of variance revealed significant interactions ( p < 0.001) where 3-RIR better maintained repetitions and work at greater average velocity (+0.6 m·s −1 ) and lower RPE (0-RIR = 10; 3-RIR = 8.2) across all sets. No differences were seen between conditions for CK at 6 hours postexercise (3-RIR: 32.2 ± 55.3%; 0-RIR: 40.8 ± 66.0%) or for CK and barbell kinetics at 24 hours to 72 hours postexercise. Although no differences were seen for recovery, the RIR strategy enabled work to be better sustained across sets at a lower perceived effort and higher average velocity. This strategy could be used to manage fatigue and better sustain effort and volume during a resistance training session.